1980
DOI: 10.1111/j.1469-7998.1980.tb04215.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution, identification, and naming of the Mastomys natalensis species complex in southern Africa (Rodentia: Muridae)

Abstract: Three hundred and forty seven rats belonging to the Mastomys natalensis complex (Smith, 1834) were live trapped from 60 localities in southern Africa. They were identified as species A, or B using either or both diploid chromosome number and haemoglobin electromorphs. These, and previously published data are presented to give a distribution of the species in southern Africa. It is suggested that workers may safely use the haemoglobin marker for identification purposes in this region as opposed to the more diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Finally, CAPANNA et al (1982) found it also in Somalia. GREEN et al (1980) proposed a systematic revision of the genus Mustomys for Southern Africa based on the comparison of type localities and karyotype distributions. They conclude that the 2n = 36/NFa = 56 morph should be attributed to the M .…”
Section: Species Attributionmentioning
confidence: 99%
“…Finally, CAPANNA et al (1982) found it also in Somalia. GREEN et al (1980) proposed a systematic revision of the genus Mustomys for Southern Africa based on the comparison of type localities and karyotype distributions. They conclude that the 2n = 36/NFa = 56 morph should be attributed to the M .…”
Section: Species Attributionmentioning
confidence: 99%
“…Mastomys natalensis (sensue lato) occurs commonly throughout most of South Africa. It was incorrectly considered as a single species but cytogenetically and electrophoretical studies during the late 1970s and early 1980s revealed the presence of two electrophoretically distinct types (2n = 32/"slow" hemoglobin electromorph and 2n = 36/ "fast" hemoglobin electeromorph), (Green et al, 1980;Gordon and Watson, 1986). These two cytotypes have also been reported to differ in sperm and bacular morphology, reproductive behaviour, pheromones and ultrasonic vocalization (Skinner and Smithers, 1990;Musser and Carleton, 1993;Smit et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For specimens collected in the early years of the JERBE activity, species identification was carried out using cytogenetic methods. Individual Mastomys species of eastern Africa are well distinguished by their karyotypes: M. awashensis -2n = 32, FNa = 54; M. erythroleucus -2n = 38, FNa = 50-56; M. natalensis -2n = 32, FNa = 52-54 (Green et al 1980, Lavrenchenko et al 1998. Two species with 32 chromosomes, M. natalensis and M. awashensis, differ by the number of metacentric and submetacentric elements, C-banding pattern and the form of the Y-chromosome (see Lavrenchenko et al 1998).…”
Section: Sampling and Species Identificationmentioning
confidence: 99%